The Activities Changing the State of The Object in the Machining and Assembling Process and their Formalization - Samek, Andrzej (Communications - Scientific letters of the University of Zilina, 2000)
The machining and assembling processes are discrete sequences of activities causing the change of semi-products into the finished parts, and assembling the parts into the final product. In computer aided process planning the precise and formalized description of activities is necessary. In the paper a conception of formalization of the activities changing the part characteristic is presented. The proposed description may be useful for process planning.